Analysis on Human Resources, Facility and Infrastructure, and Planning to Decrease the Incidence Rate of Malaria in Batu Bara Regency - Teguh Rahardjo; Irnawati Marsaulina; Nurmaini (Britain International for Academic Research (BIAR) Publisher, 2020)
Malaria is one of public health problems throughout the world, including Indonesia. Nationally, Annual Parasite Incidence (API) decreased to 0.99 per mil in 2017, but there are some malaria villages with API above the national rate. Batu Bara Regency is categorized as an endemic area and not malaria elimination with API of 0.47 per mil in 2018. The objective of the research was to analyze human resources, facility and infrastructure, and planning to decrease the incidence rate of malaria in Batu Bara Regency. The research used qualitative research method by conducting in-depth interviews with eight informants. The study found that there were no entomology assistant, malaria cadres for villages, and microscopist in the Health Agency, and of the 15 puskesmas (Primary Health Care), only five of them had microscopists. There was no transportation facility for personnel; there were only three spraycans although it should have been eight of them needed. Handling planning was not based on the mapping for detecting mosquito breeding places. The conclusion was that human resources were still unstandardized, there was no facility and infrastructure for malaria personnel. It’s suggested to mapping mosquito breeding and spraycans should be added.